PENGEMBANGAN KAWASAN PESISIR PULAU KARIMUN BESAR DALAM MENGHADAPI PERUBAHAN IKLIM - Anita Kurniasari; Fablillah Kurniawansyah; Putri Sri Wahyuni; Vilda Agustina Ayu; Virgi Selki Susiani; Asa Bintang Kapiarsa; Ivan Tofani; Tiuridah Silitonga; Diky Budiman (JURNAL PELITA KOTA, 2023)
The phenomenon of coastal problems facing climate change in the coastal area of the Coastal Area has an impact on natural changes. Climate change has the potential to cause flooding through increased rainfall and increased sea levels due to melting ice at the Earth's poles (Satterthwaite, 2008). The coastal area includes the coastline, beaches and sea waters near the coast. The series is described in the following sectors: Natural resources, infrastructure, tourism economy, socio-culture and natural disasters. According to the National Survey and Mapping Coordinating Agency (BAKOSURTANAL) the boundaries of coastal areas are areas where there is still the influence of maritime activities and as far as concentration (village) ) fisherman. For planners, climate change is a form of uncertainty, so that the issue of climate change is the main focus for all parties (Zandvoort, et al., 2018; in Fekri, 2018). The type of research used is descriptive qualitative method. The location of this research is in the administrative area of the Coastal Area. This article uses a SWOT analysis and a Likert scale.